Production of a high molecular weight levan by Bacillus paralicheniformis, an industrially and agriculturally important isolate from the buffalo grass rhizosphere - TOKSOY ÖNER, EBRU (My University, 2022)
A new exopolysaccharide (EPS) producing Gram-positive bacterium was isolated from the rhizosphere of Bouteloua dactyloides (buffalo grass) and its EPS product was structurally characterized. The isolate, designated as LB1-1A, was identified as Bacillus paralicheniformis based on 16S rRNA gene sequence and phylogenetic tree analysis. The EPS produced by LB1-1A was identified as a levan, having beta(2 -> 6) linked backbone with beta(2 -> 1) linkages at the branch points (4.66%). The isolate LB1-1A yielded large amount (similar to 42 g/l) of levan having high weight average molecular weight (Mw) of 5.517 x10(7) Da. The relatively low degree of branching and high molecular weight of this levan makes B. paralicheniformis LB1-1A a promising candidate for industrial applications.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; Mikrobiyoloji; Yaşam Bilimleri (LIFE); MICROBIOLOGY; Life Sciences (LIFE); Bacillus paralicheniformis; Exopolysaccharide; Fructan; Fructooligosaccharide; Levan; STRUCTURAL-CHARACTERIZATION; ANTITUMOR-ACTIVITY; FRUCTANS; INULIN; FRUCTOOLIGOSACCHARIDES; LEVANSUCRASE; PREBIOTICS; PHYLOGENY; GROWTH; Bacillus paralicheniformis; Exopolysaccharide; Fructan; Fructooligosaccharide; Levan